Evaluation of poly aluminium chloride (PAC) and polyacrylamide (PAM) in coagulation-flocculation processes for sewage wastewater treatment / Siti Halwa Othman, Noor Fauziyah Ishak and Muhammad Iqhmal Borhan - Othman, Siti Halwa; Ishak, Noor Fauziyah; Borhan, Muhammad Iqhmal (Universiti Teknologi MARA, 2024)
The increasing population and industrial activities in Malaysia are putting strain on the country’s sewage wastewater treatment, leading to environmental pollution and public health risks. Indah Water Konsortium Sdn. Bhd. has been commissioned assigned with sewage treatment plant (STP) operation which uses biological process of Sequence Batch Reactor (SBR). Meanwhile, research on chemical process for the sewage treatment using poly aluminium chloride (PAC) and polyacrylamide (PAM) that acted as coagulant and flocculant respectively, in Jar Test method was carried out. The purpose of this research was to evaluate the possible improvement of chemical process on suspended solids removal beyond the capabilities of the existing SBR system. These two chemicals were varied in dosage amount, and used to ensure the suspended solids are bound together to form a bigger floc and settle out. Turbidity, Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD), Total Suspended Solid (TSS) and pH value were analysed to meet the standard B limit set by the Department of Environment (DOE).